Optimized and Validated RP-HPLC Method for the Determination of Clopidogrel in Bulk and Pharmaceutical Formulation - Akter, R.; Banik, S.; Ghosh, A.; Rashid, M. M. O. (Journal of Scientific Research, 2016)
This study was undertaken to develop a novel, simple, rapid, accurate and precise sensitive reverse phase HPLC method for estimating Clopidogrel in bulk and pharmaceutical dosage form. The current method in this study was achieved by Thermo Hypersil RP C-18 column (100 mm x 4.6 mm, 3.5 µm) using a mobile phase of Phosphate Buffer: Acetonitrile (pH 3.0) is 70: 30 at a column temperature of 25°C. The effluent was monitored by UV detector at 238 nm. The retention time of Clopidogrel was 4.75 min with a flow rate 1.0 mL/min. Calibration curve was linear in the range of 10-60 µg/mL. The method was validated for linearity, precision, robustness and accuracy as per ICH guidelines. The results of all the validation parameters were well within their acceptance values (%RSD <2.0 specified by the USP, ICH and FDA), which prove applicability of the proposed method for routine analyses and quality-control assay of Clopidogrel in pharmaceutical preparations.